The Influence of Traditional Games on the Character of Elementary School Students - Hasmarita, Sony; Yusuf Nursyamsi, Muhamad; Ferrari Valentino, Ricky; Gunawan, Gugun (Universitas Pendidikan Indonesia, 2023)
The aim of this research was to determine the influence of traditional games on the character of elementary school students. This study employed a quantitative experimental research method with a one-group pretest-posttest design. The population of this study were the fifth-grade students of SDN Gunung Geulis. The sample consisted of 10 individuals. The sampling technique used in this study was the purposive sampling. The instrument was an assessment instrument for elementary school student character. The research results demonstrate a significant improvement in the pretest and posttest scores, with a t-value of 4.011 and significance value of 0.03 0.05. Thus, it concludes that there was a significant influence of traditional games on the character of elementary school students. The traditional game model can be employed by teachers to enhance the character of elementary school students.